Induction of callus and protocorm-like bodies (PLBs) in Phalaenopsis gigantea - Niknejad, Azadeh; Abdul Kadir, Mihdzar; Kadzimin, Saleh; Abdullah, N. A. (Sarawak Biodiversity Centre, 2008)
An efficient and reproducible method for large-scale propagation of Phalaenopsis gigantea using leaf sections has been developed. Leaf sections from young plants were cultured on New Dogashima medium (NDM) supplemented with cytokinins (6-Benzylaminopurine (BAP), thidiazuron (TDZ), and kinetin (KIN), each at 0.01, 0.1, 0.5 and 1.0 mgL-1) alone and in combinations with (auxins anaphthaleneacetic acid (NAA), at 0.01, 0.1, 0.5 and 1.0 mgL-1). The explants developed calli and protocorm-like-bodies (PLBs) within 8 weeks of culture. Treatment TDZ in combination with auxins was found to be best for the induction of callus and PLBs.